Digestate in paddy soil – methane emission and carbon sequestration - Bente Foereid; Maria Dietrich; Monica Fongen; Lisa Paruch (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Soils are the largest store of carbon in the biosphere, but soils can also act as the key sources of greenhouse gases. Rice cultivation in paddy soil is anoxic, thus creating an optimal condition for methane production. Digestate, a potential biofertilizer, contains a microbial consortium adapted for methane production because it comes from biogas production where methane production is optimised. In this study, we explored digestate as fertiliser in paddy soil, focussing on the effects of carbon sequestration and methane emission.